Enhanced Tensile properties of Stone wool fiber-reinforced high density polyethylene (HDPE) Composites - Subramonian, Sivarao; Mallisi, R; Teng, L S (Carl Hanser Verlag, 2014)
In this study, a minerl fiber composite of stone wool reinforced high density polyethylene (HDPE) with different weight percentage was tested. For preparation of the samples a hot pressing technique was used. Significant improvement of the tensile strength was observed for composites of stone wool HDPE with a fiber content of 20wt %. The fracture surface of the samples were analyzed for their inter layer bounding by SEM.